THE EFFECT OF THE DURATION OF GADGET PLAYING ON THE EMOTIONAL DEVELOPMENT OF CHILDREN IN THE KIDS ROOM OF MOJOWARNO KRISTEN HOSPITAL - Ana Farida Ulfa; Rina Agustin; Praise, Praise (International Journal of Social Science, 2023)
Many parents thought that gadgets could be safe and easy to supervise playmates. In fact, if viewed from the point of view of mental health science, the natural growth and development process experienced by children can be disrupted due to the use of gadgets, including children's emotional development. The purpose of this study was to determine the effect of the duration of playing gadgets on children's emotional development. The research design used correlation analytic with cross sectional approach. The population of this study were all children aged 1 -5 years in the Children's Room, Mojowarno Hospital, a total of 34 children with purposive sampling technique obtained a sample of 32 respondents. The research instrument is a questionnaire on the duration of the use of gadgets and a Questionnaire for Mental Emotional Problems, the data were analyzed by Spearman Rho Test. The results showed that most of the children used gadgets in the moderate category (60-120 minutes) a day, namely 19 children (69.4%), almost all children did not experience emotional development disorders, namely 28 children (87.5%). The results of the analysis with the Spearman Rho test showed that p-value = 0.001 or less than (0.05) and r-value = - 0.552 so that there was a relationship between the duration of using gadgets and the emotional development of children at Mojowarno Christian Hospital where the longer they use gadgets, the more they experience children's emotional development disorders. This was because by using gadgets excessively, children would lack empathy and concern for the surrounding environment, sometimes children cry and got angry for no reason if their wishes are not obeyed, especially if they asked to play gadgets. It was hoped that health workers could provide direction or education to parents who had toddlers on how to wisely introduce gadgets to children